Proceedings of the 10th ACM Symposium on Modeling, Analysis, and Simulation of Wireless and Mobile Systems 2007
DOI: 10.1145/1298126.1298195
|View full text |Cite
|
Sign up to set email alerts
|

An inhomogeneous spatial node distribution and its stochastic properties

Abstract: Most analysis and simulation of wireless systems assumes that the nodes are randomly located, sampled from a uniform distribution. Although in many real-world scenarios the nodes are non-uniformly distributed, the research community lacks a common approach to generate such inhomogeneities. This paper intends to go a step in this direction. We present an algorithm to create a random inhomogeneous node distribution based on a simple neighborhood-dependent thinning of a homogeneous Poisson process. We derive some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 12 publications
2
39
0
Order By: Relevance
“…In the space domain, on the other hand, while there are many papers concentrating on the modeling of base station locations using stochastic geometry [2], [15], there are only few works in the literature which take into account the heterogeneous spatial distribution of traffic demand in wireless cellular networks [16]- [22]. To the best of the authors' knowledge, none of the existing works provides a statistically adjustable model representing a variety of possible scenarios for UE distribution.…”
Section: B Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In the space domain, on the other hand, while there are many papers concentrating on the modeling of base station locations using stochastic geometry [2], [15], there are only few works in the literature which take into account the heterogeneous spatial distribution of traffic demand in wireless cellular networks [16]- [22]. To the best of the authors' knowledge, none of the existing works provides a statistically adjustable model representing a variety of possible scenarios for UE distribution.…”
Section: B Related Workmentioning
confidence: 99%
“…In [16], Bettstetter et al, presented an algorithm to create a random inhomogeneous node distribution based on a neighborhood-dependent thinning approach in a homogeneous PPP. The model, however, can not be used for generating BScorrelated UE patterns, as this is beyond the scope of that model.…”
Section: B Related Workmentioning
confidence: 99%
“…Figure 22 shows the impact of varying camera density when targets are deployed in a clustered manner. To generate clustered distribution of targets, we use the existing algorithm to generate inhomogeneous node distributions [Bettstetter et al 2007]. It can be observed that the coverage achieved by Hierarchical is always greater than that of DFA, and it closely tracks the Optimal, which shows that Hierarchical performs better even for the clustered distribution of targets.…”
Section: Impact Of Camera and Target Placementmentioning
confidence: 99%
“…Bettstetter et al [12] place nodes in accordance with the uniform process and then apply thinning to it. Onat and Stojmenovic [13] developed several algorithms that create connected topologies with high probability and allow user to choose the average node degree.…”
Section: Node Placement Modelsmentioning
confidence: 99%
“…In order to provide good fit between the target degree distribution and the degree distribution of the end-result topology, before a node is actually added to the topology in an iteration, several candidate nodes are evaluated (lines [6][7][8][9][10][11][12][13][14]. The number of evaluated candidates per iteration is defined by the algorithm parameter retry.…”
Section: Algorithm Descriptionmentioning
confidence: 99%